Maintaining Taxpayer Compliance in Nation Development in The Post-Pandemic Era - Ida I Dewa Ayu Manik Sastri; Desak Rurik Pradnya Paramitha Nida; I Gusti Agung Praba Mahadewi (Universitas Warmadewa, 2022)
This study aims at examining the effects of awareness, knowledge, service quality and tax sanctions on corporate taxpayer compliance. Population in this study consists of corporate taxpayers at Kantor Pelayanan Pajak Pratama Denpasar Barat with a sample of 100 respondents and 3 key informants. Sampling in this study was done using nonprobability sampling method, with incidental sampling technique. The type of research data is primary data, which was obtained through questionnaires answered by corporate taxpayers. Data were analyzed using comparative descriptive qualitative techniques and Multiple Linear Regression Analysis. From the results of the study it was found that: (1) awareness has a positive and significant effect on corporate taxpayer compliance; (2) knowledge has a positive and significant effect on corporate taxpayer compliance; (3) service quality has a positive and significant effect on corporate taxpayer compliance; and (4) tax sanctions have a positive and significant effect on corporate taxpayer compliance. The magnitude of the influence of the independent variable on corporate taxpayer compliance is 71%, while the remaining 29% is influenced by other factors outside the model studied. The results of the descriptive test uncover that corporate taxpayers are categorized as compliant. Whatever the conditions, whether high or low education and the presence or absence of adequate services, taxpayers still carry out their obligations as well as possible, because they already have a good awareness of the importance of paying taxes. Tax sanctions are something frightening and the taxpayers do not want to be subject to it.